2020
DOI: 10.1007/s11042-020-09771-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimally configured convolutional neural network for Tamil Handwritten Character Recognition by improved lion optimization model

Abstract: In recent data, Optical character recognition (OCR) systems have laid hands in the field of most popular language recognitions. Unlike other languages, the Tamil language is more complex to recognize, and hence considerable efforts have been laid in literature. However, the models are not yet well-organized for precise recognition of Tamil characters. Thus, the current research work develops a novel Tamil Handwritten Character Recognition approach by following two major processes, viz. pre-processing and recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The availability of a comprehensive database can also help to objectively assess the true efficacy/limitations of SOTA algorithms [18]. Developing a robust Tamil OCR system necessitates a large and extensive database [10]. As mentioned earlier, there is only a single standardized database developed by HP labs India, available for the Tamil OCR domain [18].…”
Section: B Existing Tamil Handwritten Databasementioning
confidence: 99%
See 2 more Smart Citations
“…The availability of a comprehensive database can also help to objectively assess the true efficacy/limitations of SOTA algorithms [18]. Developing a robust Tamil OCR system necessitates a large and extensive database [10]. As mentioned earlier, there is only a single standardized database developed by HP labs India, available for the Tamil OCR domain [18].…”
Section: B Existing Tamil Handwritten Databasementioning
confidence: 99%
“…Tamil Handwritten character recognition is one such challenging research topic for close to 4 decades now [7], [8]. Despite this, it continues to offer many challenges which keeps the research community active even till date [9], [10]. The OCR of printed documents has been considered a problem solved par human accuracy or even better [11]- [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain better understanding, the highlights of few research works are delineated in the following section. Lincy et al (2020) demonstrated an optimal configuration of convolutional neural network for Tamil Handwritten Character Recognition using an improved lion optimization algorithm. The evaluation measures employed in recognizing the Tamil characters were Accuracy, sensitivity, specificity and precision.…”
Section: Existing Studies Based On Tamil Character Recognitionmentioning
confidence: 99%
“…This section discusses the comparative results of various simulation metrics namely accuracy, sensitivity, specificity and F1-score for various existing Tamil character recognition approaches namely Neural network base Elephant herding optimization (NN-EHO) (Kowsalya and Periasamy, 2019), Convolution Neural Network-based Improved Lion optimization (CNN-ILO) (Lincy et al 2020), Convolution neural networks (CNN) and Modified Convolution neural networks (MCNN). Fig.…”
Section: Comparative Analysismentioning
confidence: 99%